2022
DOI: 10.3389/fpsyt.2022.995669
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive reappraisal training for parents of children with autism spectrum disorder

Abstract: Parents of children with autism spectrum disorder (ASD) experience higher stress levels than those of typically developing children. The goal of the current study was to examine whether a mentalization-based intervention would enhance parental cognitive reappraisal, an adaptive form of emotion regulation associated with lower levels of stress. Findings from 27 parents who completed a short training indicated an improvement in cognitive reappraisal. In exploratory analyses, two different types of reappraisal we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Gross argues that cognitive reappraisal (CR) is an effective way to regulate emotions. It involves changing the evaluation of situational cues to alter the trajectory of emotional responses, often to interpret negative emotions such as frustration, anger, or disgust more positively, or rationalizing emotional events [38]. In this study, good family adaptation provides flexible cognitive resources for the development of Zhongyong thinking style, and cognitive reappraisal can affect emotions through the cognitive way of meaning [39] and relieve the intensity of anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Gross argues that cognitive reappraisal (CR) is an effective way to regulate emotions. It involves changing the evaluation of situational cues to alter the trajectory of emotional responses, often to interpret negative emotions such as frustration, anger, or disgust more positively, or rationalizing emotional events [38]. In this study, good family adaptation provides flexible cognitive resources for the development of Zhongyong thinking style, and cognitive reappraisal can affect emotions through the cognitive way of meaning [39] and relieve the intensity of anxiety.…”
Section: Discussionmentioning
confidence: 99%
“…Neurologists have further corroborated the mode of action of different emotion regulation strategies through functional MRI, potential recognition, and more (27,28). Emotion regulation strategies have been applied in neurological disorders treatment, time perception, and psychological support and interventions (29)(30)(31). Studies have shown that cognitive reappraisal is beneficial in relieving emotions such as anxiety and depression, while expression suppression has the opposite effect (32)(33)(34).…”
Section: Introductionmentioning
confidence: 98%